Four new mitochondrial genomes for the basal bee family Melittidae (Hymenoptera: Apoidea). Issue 2 (1st February 2021) - Nickel, Jana; Reinbold, Carla Violetta; Kuhlmann, Michael; Cordellier, Mathilde; Husemann, Martin
Abstract: We present four new complete mitochondrial genomes for Dasypoda hirtipes, Melitta schultzei, Capicola nanula and Samba griseonigra belonging to the basally branching bee family Melittidae covering four genera in three tribes (Melittini, Hesperaspini, Dasypodaini) and two subfamilies (Melittinae, Dasypodainae). The mitogenomes vary between 15, 884 and 20, 324 bp in length and consist of the typical set of 13 protein-coding genes, 22 tRNAs, two rRNAs and the control region. These new mitogenomes raise the number of available mitochondrial genomes for the family Melittidae to five and will help to shed light on the phylogenetic relationships within Melittidae and their position within the Anthophila.